The Investigation of 3D Magnetic Field Distribution in Multilayer Coils - Grainys, A.; Novickij, J. (Elektronika ir Elektrotechnika, 2010)
The investigation of magnetic field distribution via x-y-z directions of multilayer coils has been carried out. Finite elements method was used for numerical simulation of magnetic field components. The model was verified experimentally using experimental PC controlled equipment. The control algorithm for automatic measurements was developed using LabView programming package. It allows to map a magnetic field at any point over any surface moving a 3-axis magnetic probe through a three dimensional volume while measuring the three orthogonal components of magnetic field strength at designated points and magnetic field distribution profiles can be plotted. The experimental and simulation results were compared and acceptable compliance has been achieved. The results provide a possibility to forecast parameters of multilayer coils avoiding expensive and long lasting experiments.